Increasing skills reading students through guidance and counseling classical using Contextual Teaching and Learning (CTL) approach - Romi Fajar Tanjung; Neviyarni Neviyarni; Firman Firman (International Journal of Research in Counseling and Education, 2019)
Counseling has been such a trend in 21 century, as a science that studied a human in psychology perspective. However, it appear with progressive touch, has affect in human mindset in every life that undertake. In 21 century development, many opinion and argumentation about counseling has an uniqueness in philosophy multicultural perspective that counseling has linkage with cultural and philosophy values in human it self, that make a new paradigm has been raise to the surface, such indigineous counseling and multicultural counseling perspective. Regardless with that paradigm, we can’t deny that basically all of science was from a human philosophy about their life with purpose to make understand and handle their life with solving a problems. But it is not all of cultural and philosophy values can be a such formulation to solve a problems, and if it can be transform to such formulation as a science, there are a procedure and criteria to be needed. Also if a counseling as a philosophy or science and also practical intervention, how to implemented in real life with a multicultural and multivalues in philosophy of life. In this article, will describe more further such a synthesize that counseling can be a science or practical science in educational multicultural philosophy paradigm and a result found that 27 (45%) counselor perception about counseling profession that as educational practice.